2015
DOI: 10.2967/jnumed.115.160481
|View full text |Cite
|
Sign up to set email alerts
|

Time Evolution of DOTATOC Uptake in Neuroendocrine Tumors in View of a Possible Application of Radioguided Surgery with β Decay

Abstract: A novel radioguided surgery (RGS) technique exploiting β − radiation has been proposed. To develop such a technique, a suitable radiotracer able to deliver a β − emitter to the tumor has to be identified. A first candidate is represented by 90 Y-labeled DOTATOC, a compound commonly used today for peptide radioreceptor therapy. The application of this β − RGS to neuroendocrine tumors (NET) requires study of the uptake of DOTATOC and its time evolution both in tumors and in healthy organs and evaluation of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 14 publications
4
29
0
Order By: Relevance
“…This is indeed the level of agreement of the predictions close to the skin and on the tumor bulk. This assessment strengthens the feasibility studies on meningioma, glioma and neuro-endocrine tumors already published [9,10].…”
Section: Discussionsupporting
confidence: 83%
“…This is indeed the level of agreement of the predictions close to the skin and on the tumor bulk. This assessment strengthens the feasibility studies on meningioma, glioma and neuro-endocrine tumors already published [9,10].…”
Section: Discussionsupporting
confidence: 83%
“…The study of the uptake of the radiotracer nearby the lesion showed that a tumor-non-tumor ratio (TNR) greater than 10 is observed in almost all the cases and a detailed simulation of the intraoperative probe allowed predictions of the RGS performance that resulted as very promising. Similar conclusions were recently achieved on neuro-endocrine tumors [7].…”
Section: Introductionsupporting
confidence: 79%
“…With respect to the specific type of detected radiation, they can be divided in g probes, the only ones widely diffuse in the surgical practice b -probes, and PET probes, detecting radiations originating from positron emitters [14][15][16][17][18].…”
Section: Detection Probe Systemsmentioning
confidence: 99%